CHEMICAL COMPOSITION “OF JUGLANS REGIA L” PLANT AND SIGNIFICANCE IN FOLK MEDICINE (Scientific journal of the Fergana State University, 2024)
This article analyzes the botanical and biological properties of the walnut Juglans regia L growing in the Fergana Valley, the medicinal properties of plant leaves, i.e. their role in folk medicine. The main focus is on the study of the chemical composition of the leaves of Juglans regia L., especially the content of water-soluble vitamins and their importance in the treatment of certain diseases in the human body, and the amount of vitamins in the leaves of the plant was determined by high performance liquid chromatography.